Taxing data as an instrument of economic digital constitutionalism: elements for a normative agenda - Angelo Jr Golia (European Law Open)
Digital constitutionalism rarely focuses on value creation, extraction, and distribution. This Article introduces a symposium that contributes to filling this gap, using data taxation as an entry point and sketching the elements of a normative agenda. The contributions advance different proposals, but they share the view that the externalities of informational capitalism have constitutional significance. Based on this, this introduction keeps four issues together: (1) the impact of excessive datafication on contemporary societies; (2) the role of data in contemporary economy; (3) concrete tax design; (4) the interaction of data taxation with other legal regimes and social justice issues, also at the global level. The first goal is to increase the dialogue among strands of legal scholarship that do not necessarily speak the same language. The second goal is to expand the analytical and normative scope of digital constitutionalism, which cannot address such issues as accidental elements but needs to be (also) an economic constitutionalism. The Article proceeds as follows. Section 2 focuses on the link between the digital revolution and constitutional states, especially on their role in value creation, extraction, and distribution. Section 3 identifies such an issue as a gap in digital constitutionalism and opens the way to the following sections. Section 4 is divided into four subsections. Section 4.A stresses the need for critical approaches to datafication, which needs to be seen as an autonomous object of regulation. Section 4.B highlights the role of data within contemporary economy and offers normative justifications for its taxation. Section 4.C highlights the need to include Pigouvian, progressive, and rent-targeting elements into data tax design. Section 4.D puts these issues within the context of economic governance, highlighting the role of (global) institutions in creating, extracting, and distributing value as well as the political nature of the underlying policy choices. Section 5 concludes.